2008
DOI: 10.1016/j.jasms.2007.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Direct quantitation of active ingredients in solid artesunate antimalarials by noncovalent complex forming reactive desorption electrospray ionization mass spectrometry

Abstract: The direct quantitation of active ingredients in solid pharmaceutical tablets by desorption electrospray ionization mass spectrometry (DESI MS) is complicated by the dependence of the DESI signal on variables such as spray angles and distances, morphological sample properties, and the difficulty of properly incorporating an internal standard. Here, a DESI MS method for the direct quantitative screening of widely counterfeited antimalarial tablets containing artesunate is presented. This method is based on reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 22 publications
0
61
0
Order By: Relevance
“…Similarly, the ketones formed as oxidation products probably could be detected using hydroxylamine [21] or long-chain amines [22] as derivatizing agents. This was judged unnecessary given that the needed information was obtained from the alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the ketones formed as oxidation products probably could be detected using hydroxylamine [21] or long-chain amines [22] as derivatizing agents. This was judged unnecessary given that the needed information was obtained from the alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…These data should be considered semiquantitative, because previous DESI-MS studies have shown that signal intensity is influenced to some extent by surface morphology (38); hence, data are truly quantitative only across identical, homogenous surfaces-a feature not inherent to most biological materials. Despite these limitations, with an antifungal IC 50 value of approximately half the measured surface concentration of bromophycolides on patches, it is probable that (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…This is referred to as "reactive DESI" [203][204][205][206][207] and it has been used for the detection of cholesterol and other 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 33 hydroxyl-functionalized non-polar lipids such as steroids and some vitamins. Due to its low polarity and lack of ionizable functional groups, intact cholesterol is not readily observed by electrospray-based methods.…”
Section: Desorption Electrospray Ionization (Desi)mentioning
confidence: 99%